Impact of histology on prognosis of patients with early-stage cervical cancer treated with radical surgery - Rudtanasudjatum K. (2014)
Objective: To examine the effect of carcinoma cell type on tumor characteristics, tumor spread, tumor recurrence, and survival of patients with early-stage cervical cancer who had radical hysterectomy and pelvic lymphadenectomy. Method: Data from 499 patients with stage IA to IIA cervical carcinoma who received primary surgical treatment from 2003 to 2005 at Chiang Mai University were retrospectively reviewed with regard to 3 histologic types; squamous cell carcinoma (SCC), adenocarcinoma (AC), and adenosquamous carcinoma (AS). Results: Among the 499 patients, 71.1% had SCC, 23.4% had AC, and 5.4% had AS. There was no significant difference in stage, tumor size, tumor characteristics, or rate of loco-regional spread. A higher proportion of women with SCC needed adjuvant radiation (P = 0.001). Five-year recurrence-free survival (RFS) and overall survival (OS) were comparable among the groups. Among patients with pelvic node metastasis, 5-year RFS and OS were significantly lower in those with AC than in those with SCC (RFS, 66.1% versus 86.4%, P = 0.02; OS, 68.2% versus 88.2%, P = 0.05). Conclusion: There was no difference among SCC, AC, and AS in most tumor characteristics, spread, recurrence, and survival in patients with early-stage cervical cancer. Among patients with pelvic lymph node metastasis, AC was associated with less favorable outcomes than SCC. © 2011 International Federation of Gynecology and Obstetrics.